2022
DOI: 10.3390/ijerph192113765
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Passive Sedentary Behavior among Community-Dwelling Older Women with and without Knee Osteoarthritis: The Otassha Study

Abstract: Passive sedentary behavior (SB) may lead to adverse health outcomes; however, it remains unclear whether the factors relevant to passive SB differ between older adults with and without knee osteoarthritis (KOA). This cross-sectional study examined factors associated with passive SB among 688 community-dwelling older women with (n = 128) and without (n = 560) KOA. Passive SB (min/day) was assessed using the Japanese-translated version of the Measure of Older Adults’ Sedentary Time questionnaire. Demographic, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
2
Order By: Relevance
“…The current study found a significant positive association between arthritis and sedentary behavior independent of diabetes mellitus status. Our research findings contradict those of a previous study that reported similar sedentary behavior levels between older women with and without knee osteoarthritis [44]; however, the previous study did not adjust for potential confounders and included only older women. A recent study of individuals with rheumatoid arthritis suggested that disease activity indirectly influences sedentary behavior through pain intensity [45].…”
Section: Discussioncontrasting
confidence: 99%
“…The current study found a significant positive association between arthritis and sedentary behavior independent of diabetes mellitus status. Our research findings contradict those of a previous study that reported similar sedentary behavior levels between older women with and without knee osteoarthritis [44]; however, the previous study did not adjust for potential confounders and included only older women. A recent study of individuals with rheumatoid arthritis suggested that disease activity indirectly influences sedentary behavior through pain intensity [45].…”
Section: Discussioncontrasting
confidence: 99%
“…Although previous studies have reported that sedentary times are long in patients with osteoarthritis or rheumatoid arthritis [42,43], few studies have compared the sedentary behaviour of this population to matched control groups. In a cross-sectional study of older women, no significant difference was found in the mean total sedentary times between women with and without knee osteoarthritis [44]. Although this finding is not consistent with the findings of our study, that study did not adjust for confounding factors and simply compared the mean sedentary time.…”
Section: Discussioncontrasting
confidence: 97%
“…Having a sedentary lifestyle is globally recognized as a cause for many chronic diseases [ 3 , 5 , 8 , 9 , 10 , 34 , 35 , 36 , 37 ]. The present data show that sedentary lifestyle is also significantly associated with higher levels of alcohol drinking, another high-risk factor of lifestyle.…”
Section: Discussionmentioning
confidence: 99%